The burden of hostility in U.S. Veterans: Results from the National Health and Resilience in Veterans Study. (30th September 2016) - Sippel, Lauren M.; Mota, Natalie P.; Kachadourian, Lorig K.; Krystal, John H.; Southwick, Steven M.; Harpaz-Rotem, Ilan; Pietrzak, Robert H.
Abstract: Hostility is associated with substantial mental and physical health consequences. Population-based data regarding the nature and longitudinal course of hostility in U. S. veterans are scarce. We analyzed data from 2157 U. S. veterans who participated in the National Health and Resilience in Veterans Study, a nationally representative, prospective cohort study of U. S. veterans. We identified the prevalence of longitudinal courses of hostility (chronic, increasing, decreasing, or no hostility). We then evaluated relationships between sociodemographic, risk, and protective correlates measured at baseline and longitudinal courses of two aspects of hostility—aggressive urges and difficulties controlling anger. The majority of veterans (61.2%) reported experiencing difficulties controlling anger and a sizable minority of veterans (23.9%) reported experiencing aggressive urges over a two-year period. Protective psychosocial characteristics (e.g., optimism) and aspects of social connectedness (e.g., secure attachment style) were negatively associated with hostility. Psychological distress predicted all symptomatic hostility courses, while alcohol misuse predicted chronic aggressive urges and all symptomatic courses of difficulties controlling anger. These findings provide the first known population-based evaluation of the prevalence, course, and risk and protective correlates of hostility in U. S. veterans, and suggest targets for prevention and treatment efforts that can help mitigate risk for hostility in this population. Graphical abstract: Highlights: Data from 2157 US veterans in the National Health and Resilience in Veterans study. Categorized as having increasing, decreasing, chronic, or no hostility over 2 years. Psychosocial and social connectedness variables negatively associated with hostility. Psychological distress & alcohol misuse positively associated with hostility. First population-based study of hostility prevalence, course, correlates in veterans.